Ainsliaea polystachya (Asteraceae), a new species from Fujian, China based on morphological and molecular evidence - Zhang, Mei-Jiao; Su, Xiang-Xiu; An, Chang; Li, Hong-Qing; Zhang, Zhen (Phytotaxa, 2021)
A new species, Ainsliaea polystachya X. X. Su & M. J. Zhang is described from Fujian, China, based on morphological traits and molecular markers. The new species is distinct by open panicles, capitula bearing only one flower, and actinomorphic corolla. Keys to the morphologically similar species and phylogenetic allies are proposed.